The effects of N-doping and oxygen vacancy on the electronic structure and conductivity of PbTiO3 - 牛培江 闫金良 孟德兰 (半导体学报：英文版, 2015)
By using spin-polarized density functional theory calculations, the electron density differences, band structures and density of states of p-type N-doped PbTiO3 have been studied. In addition, the oxygen vacancy in N-doped PbTiO3 is also discussed. After the nitrogen dopant is introduced into the crystal, the N-doped PbTiO3 system is spin-polarized, the spin-down valance bands move to a high energy level and the Fermi energy level moves to the top of the valance bands, finally the band gap is narrowed. In this process, the N-doped PbTiO3 shows typical p-type semiconductor characteristics. When an oxygen vacancy and N impurity coexist in PbTiO3, there is no spin-polarized phenomenon. The conduction bands move downward and the acceptors are found to be fully compensated. The calculation results are mostly consistent with the experimental data.